Factors associated with early neonatal debt in a northeast brazilian state (Research, Society and Development, 2021)
We aimed to carry out an analysis of the factors related to early neonatal deaths that occurred in the State of Ceará. Cross-sectional, analytical study, with a sample of 724 records of early neonatal deaths. We use as bases of information: Information System on Live Birthsand Information System on Mortality. We found a correlation between early neonatal death and the variables: anomaly; number of prenatal consultations; Apgar in the fifth minute. The presence of anamaly in newborns presented twice the risk when related to early neonatal death. The same was observed with regard to the number of consultations, indicating an increased risk for early neonatal mortality of approximately twice that related to pregnant women who had less than seven prenatal consultations. Another significant parameter was Apgar in the fifth minute, which showed a six-fold increase in the risk of early neonatal death. It was found that difficulties in relation to prenatal, childbirth and posrpartum were more importante for the origino f deaths. All of these issues are reflected in the attention to gestacional health, as well as during the growth and Evolution related to the newborn.